An Evaluation of the Academic Stress' Affect on Periodontal Tissues - Goleli Hulya Sariaslan; Akkaya Murat; Camgoz Melike (Balkan Stomatological Society, 2019)
Background/Aim: It has been discussed over the years whether emotional stress might be a risk factor for periodontal diseases. The correlation between periodontal disease and stress can still not be explained. Our aim was to evaluate the effects of academic stress on gingival tissues in a prospective design.